Kesantunan Berbahasa Pada Caption Dan Konten Instagram @Azkiave - Zulia Munna Khasanah; Hari Bakti Mardikantoro (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the observance and violation of Leech’s politeness principles, as well as the factors causing the violations in the comment section of @azkiave. This research employed a descriptive qualitative approach using observation and note-taking techniques. The data were analyzed through pragmatic and normative matching methods. The findings revealed 154 utterances that complied with the maxims of tact, modesty, approbation, generosity, apology, sympathy, opinion, and agreement. Violations were identified in the maxims of modesty, approbation, sympathy, feeling, opinion, and agreement. The factors that cause the violations included direct criticism using harsh words, the speaker’s emotional push, protective attitudes toward personal opinions, intentional accusations toward interlocutors, and deliberate attempts to corner interlocutors.